2020
DOI: 10.1088/1361-6528/aba3d9
|View full text |Cite
|
Sign up to set email alerts
|

Nickel cobalt oxide nanowires with iron incorporation realizing a promising electrocatalytic oxygen evolution reaction

Abstract: Developing cost-effective electrocatalysts for water electrolysis is a promising strategy to enhance conversion and storage efficiency of sustainable energy. Transition metal oxides have been considered as alternative oxygen evolution reaction (OER) catalysts to replace noble metal-based catalysts. Here, we report a series of Fe-doped NiCo 2 O 4 (NCO) nanowires with different Fe-doped concentrations, synthesized by a facile solvothermal and calcinations process, as high-efficiency electrocatalysts for OER. Due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 49 publications
(51 reference statements)
1
12
0
Order By: Relevance
“…The shift suggests successful incorporation of Fe 3 + in NiCo 2 O 4 nanoparticles. Similar shift in XRD peaks in Fe-doped NiCo 2 O 4 nanowires has been reported by Hao et al [31] The crystallite size of pure NiCo 2 O 4 and iron-doped NiCo 2 O 4 nanoparticles was estimated using Scherrer formula and the values for pure NiCo 2 O 4 , FeNC-0.1-500, FeNC-0.3-500, FeNC-0.5-500 and FeNC-0.7-500 are 13.4 nm, 11.7 nm, 12.6 nm, 10.1 nm and 12.4 nm, respectively. Figure S8 depicts the Rietveld refinement of XRD patterns of iron-doped NiCo 2 O 4 nanoparticles.…”
Section: Characterization Of Iron-doped Nico 2 O 4 Nanoparticlessupporting
confidence: 88%
See 2 more Smart Citations
“…The shift suggests successful incorporation of Fe 3 + in NiCo 2 O 4 nanoparticles. Similar shift in XRD peaks in Fe-doped NiCo 2 O 4 nanowires has been reported by Hao et al [31] The crystallite size of pure NiCo 2 O 4 and iron-doped NiCo 2 O 4 nanoparticles was estimated using Scherrer formula and the values for pure NiCo 2 O 4 , FeNC-0.1-500, FeNC-0.3-500, FeNC-0.5-500 and FeNC-0.7-500 are 13.4 nm, 11.7 nm, 12.6 nm, 10.1 nm and 12.4 nm, respectively. Figure S8 depicts the Rietveld refinement of XRD patterns of iron-doped NiCo 2 O 4 nanoparticles.…”
Section: Characterization Of Iron-doped Nico 2 O 4 Nanoparticlessupporting
confidence: 88%
“…Hao et al have reported such shift towards higher binding energy after the introduction of iron in NiCo 2 O 4 nanowires. [31] The DRS results of pure NiCo 2 O 4 nanoparticles and irondoped NiCo 2 O 4 nanoparticles are depicted in Figure 6. Figure S14 shows the Tauc plots from which the band gaps of NiCo 2 O 4 and iron-doped NiCo 2 O 4 nanoparticles were determined.…”
Section: Proposed Mechanism Of Formation Of Iron-doped Nico 2 O 4 Nan...mentioning
confidence: 99%
See 1 more Smart Citation
“…Stability is used to evaluate the performance of electrocatalysts over a long period of time. The stability test was done by the constant current method (chronopotentiometry). …”
Section: Methodsmentioning
confidence: 99%
“…In particular, for the cobalt-related materials, the nanowire structures with a large surface area and promoted electric current have been suggested cardinally for water electrolysis [21][22][23][24][25][26]. The well-defined 1D nanowire arrangements enable a new configuration of highefficiency electrocatalyst/electrode due to synergistic effects such as faster electrolyte penetration and diffusion of ionic species, greater electrical conductivity, higher structural stability, and short electron transport pathway [23,[27][28][29][30]. Recently, the surface oxidation reaction for cobalt nanorod arrays was reported to be able to improve electrocatalytic properties [31].…”
Section: Introductionmentioning
confidence: 99%